The performance of young football players in terms of their respiratory function, contingent upon their position on the field - Kozhevnikov, V. S.; Alabuzhev, S. A.; Lazarenko, V. G. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to comparative analysis of the key indicators of external respiration in football players across different stages of adolescence.